Lichen sclerosus: a review of the literature and a case of an atypicsurgical treatment - Ziglioli, F.; Fornia, S.; Ciuffreda et al., M. (Acta Biomedica Atenei Parmensis, 2011)
Lichen sclerosus is a chronic immuno-mediated skin disease of the genital region in men and women. The treatment may be pharmacological or surgical, the choice depending on the extension of the involved area, the histological pattern and the level of functional disease complained by the patient. If the biopsy is negative for neoplastic degeneration the treatment may be pharmacological only. In our paper, we describe the case of a patient with vulvar disease and labial fusion, burial of the clitoris and severe introital stenosis. In this case, the treatment was surgical.